Analysis of Internal and External Factors of Transport Delay in PT Sari Dumai Oleo - Butar , Prima Alexander; Ahmed, Abdussalam Ali (Sinergi International Journal of Logistics, 2023)
This research was conducted at PT Sari Dumai Oleo. The purpose of this study is to analyze Internal and External Factors of Transportation Delay at PT Sari Dumai Oleo. In this study, researchers distributed 20 questionnaires to respondents, and these respondents were directly related to the object of research. The research methodology used in this study is quantitative research method. Based on the results of data analysis and discussion of the results of research data analysis on the influence of internal and external factors on transportation delays, it can be concluded that the results of the study show a positive and significant influence between internal and external factor variables on transportation delay variables. Based on descriptive research variables, internal and external variable factors have a grand mean value of 4.11 which is categorized at Good level and transportation delay variable has a grand mean value of 3.80 which is categorized at Good level. Internal and external variables can explain or explain the variable of transportation delay by 56.4% and the remaining 43.6% is influenced by factors that are not included in this study. Based on the results of the t test, the t-count value was obtained > t-table (6.022 > 2.048) with a significance level of 0.000 < 0.050. This means that H1 is accepted and H0 is rejected. It partially shows that internal and external factors have a significant effect on transportation delays.